Testing of Equity Portfolio Selection by Using Momentum- and Value strategies : Evidence of Nordic Markets - Ylitalo, Maria (My University, 2022)
Momentum and value investing are different investment strategies that have been researched a lot during the past six decades. The results of previous studies have slightly varied, however, finding that both strategies have indicated ability to predict future returns. While momentum strategy focuses on buying of recently well performed stocks, i.e., winners and selling the losers and is based on relatively short-term investing, value investment strategy, however, aims to find and buy undervalued stocks and hold them long-period of time. Approximately 30 years ago, Asness (1997) decided to combine these aforementioned investment strategies and found that the methodology turned out be efficient way to gain abnormal returns despite the negative correlation of these two strategies. Since then, the topic has been researched widely and for example small companies have proved their potential to provide higher abnormal returns under momentum and value investment strategy. The majority of previous studies have however focused on studying especially US and global markets, which motivates to study more recent data from the Nordic markets from the period between 2001 and 2020. The study is using quantitative research methods in which the companies are divided into six different decile portfolios based on their valuation status, i.e., value, growth and neutral. Additionally, the companies are divided into small and large portfolios based on their market value. An identical split will be repeated when using momentum and value investment strategies. The goodness of the method is measured with widely used four factor-regression model and t-test. The study finds that combining momentum and value investment strategies works efficiently and the strategies can be combined also in the Nordic markets. The model indicates similar negative correlation between the strategies as in the previous studies, however all findings are not statistically significant at acceptable conventional levels. Additionally, the results indicate that momentum and value investment strategies work especially among small companies, and the results are statistically significant in most of the decile portfolios. The last interesting finding of the study indicates that usage of balance sheet-based profitability metrics works better in value investing compared to earnings-based metrics.

Momentum- ja arvosijoittaminen ovat kaksi erilaista sijoitusstrategiaa, joita on viimeisen kuuden vuosikymmenen ajan tutkittu paljon erillisinä sijoitusstrategioina. Aiemmat tutkimustulokset ovat hieman vaihdelleet, mutta pääasiass molemmat strategiat ovat osoittaneet kykyä tulevaisuuden tuottojen ennustamisen osalta. Siinä missä momentum- keskittyy ostamaan edellisiä voittajia ja myymään häviäjiä lyhyellä ajanjaksolla arvosijoittaminen pyrkii löytämään aliarvostetut osakkeet, ostamaan ne halvalla ja pitämään niitä pitkän ajanjakson. Myöhemmin noin 30-vuotta sitten Asness (1997) päätti yhdistää kyseiset strategiat ja havaitsi yllättävän käänteen, sillä menetelmä osoittautui toimivaksi strategiaksi ansaita epänormaaleja tuottoja, näiden kahden sijoitusstrategian negatiivisesta korrelaatiosta huolimatta. Sittemmin aihetta on tutkittu entisestään ja esimerkiksi pienet yhtiöt ovat osoittaneet kykynsä tuottaa epänormaaleja tuottoja paremmin, yhdistäessä momentum- ja arvosijoittamisen strategiat. Suurin osa edellisistä tutkimuksista on kuitenkin keskittynyt analysoimaan etenkin Amerikan tai maailman laajuista markkinaa, joka motivoi tässä tutkimuksessa keskittymään nimenomaan Pohjoismaisiin osakemarkkinoihin vuosilta 2001-2020. Tutkimus toteutettiin kvantitatiivista menetelmää käyttäen, jossa yhtiöt jaettiin kuuteen erilaiseen desiili-portfolioon sen mukaan, oliko kyseessä arvo-, kasvu- vai neutraaliyhtiö. Lisäksi yhtiöt edelleen jaettiin markkina-arvoon perustuen joko suuriin tai pieniin yhtiöihin. Sama jako toistettiin sekä momentum- että arvosijoitusmenetelmää käyttäessä. Metodin hyvyys ja toimivuus puolestaan mitattiin paljon käytetyn neljän-tekijän regressiomallin ja t-testin avulla. Tutkimuksen tulokset osoittavat, että momentum- ja arvosijoitusstrategian yhdistämien toimii tehokkaasti ja strategiat ovat yhdistettävissä myös Pohjoismaiden osakemarkkinoilla. Malli osoittaa aiemmissakin tutkimuksissa havaittua negatiivista korrelaatiota strategioiden välillä, mutta tulokset eivät kaikkien portfolioiden osalta ole tilastollisesti merkittäviä. Lisäksi tulokset osoittavat, että momentum- ja arvosijoitusstrategiat toimivat etenkin pienten yhtiöiden keskuudessa. Tilastollinen merkitsevyys on tämän osalta havaittavissa lähes kaikkien desiili-portfolioiden osalta. Viimeisenä mielenkiintoisena havaintona tutkimus osoittaa, että tasepohjaiset tunnusluvut toimivat tulospohjaisia tunnuslukuja paremmin arvosijoittamisessa.
Keywords: momentum investing, value investing, momentum- and value investing, portfolio construction, investment strategy, multiples